Tissue-specific CTCF/Cohesin-mediated chromatin architecture delimits enhancer interactions and function in vivo - Hanssen, Lars L P (Nat Cell Biol, 2017)
The genome is organised via CTCF/Cohesin binding sites, which partition chromosomes into 1-5Mb topologically associated domains (TADs), and further into smaller sub-domains (sub-TADs). Here we examined in vivo an ~80kb sub-TAD, containing the mouse α-globin gene cluster, lying within a ~1Mb TAD. We find that the sub-TAD is flanked by predominantly convergent CTCF/cohesin sites which are ubiquitously bound by CTCF but only interact during erythropoiesis, defining a self-interacting erythroid compartment. Whereas the α-globin regulatory elements normally act solely on promoters downstream of the enhancers, removal of a conserved upstream CTCF/cohesin boundary extends the sub-TAD to adjacent upstream CTCF/cohesin binding sites. The α-globin enhancers now interact with the flanking chromatin, upregulating expression of genes within this extended sub-TAD. Rather than acting solely as a barrier to chromatin modification, CTCF/cohesin boundaries in this sub-TAD delimit the region of chromatin to which enhancers have access and within which they interact with receptive promoters.